Acupressure Titik SP6, LI4 dan BL32 Mengurangi Nyeri Persalinan Kala I Systematic Literature Review - shofira mufidah; Lia Ayu Kusumawardani; Siti Fadhilah (Universitas Islam Jember, 2022)
Pregnant women in Indonesia on average experience severe labor pain by 85-90%. Pain in the first stage can be influenced by physiological factors (stretching of the cervical muscles, uterine contractions, lowering of the head, and opening of the lower uterine segment) and psychological factors (stress, worry and fear). Acupressure is one way of providing stimulation by pressing certain points with the principles of acupuncture. Acupressure has many benefits such as increasing stamina, improving blood circulation, reducing stress and reducing pain. This study uses the Systematic Literature Review research method to identify and analyze 15 international journals obtained through the Pubmed, Cochrane and Science Direct databases. The results obtained are that acupressure helps mothers relax more in dealing with labor pains in stage 1. Acupressure can stimulate endorphins and increase blood circulation thereby increasing oxygen supply and can activate small nerves to block pain impulses to the brain. Acupressure can reduce pain in the first stage of labor.